PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN PERANGKAT LUNAK AUTOGRAPH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA BERASIS POLYA’S FOUR-STEP PROBLEM SOLVING - Budi Halomoan Siregar Nurliani Manurung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This research apply problem based learning model (PBM) by using autograph software in learning process of linear programming mathematics. The purpose of this study is to improve the learning process in class. Consequently, these actions can have an impact on improving problem-solving skills. This research is a classroom action research conducted on 37 students of mathematics education A 2015 in academic year 2016/2017.Furthermore, the data in this study is obtained through the process of observation and test of problem solving. The data are analyzed through three stages, namely: data reduction, data exposure, and draw conclusions. Morever, the results of this study show an increase in problem solving skills of students on indicators of understanding problems, devising a plan, carrying out the plan, and looking back the solution.Keywords: Problem Based Learning (PBM), action research class, Autograph.